Nahdlatul Ulama dan Problematika Relasi Agama-Negara di Awal Kemerdekaan RI - Hisyam, Muhamad (Jurnal Lektur Keagamaan, 2014)
The Sixth Congress of Nahdlatul Ulama (NU) 1936 in Banjarmasin decided that the region of Dutch East Indies is dar ul Islam. This decision according to Abdurahman Wahid is the ideological basis for NU in terms of religion-state relations. This article explores the extent to which ideology is implemented in NU fighting after Indonesia's independence until 1955. The NU  fighting in the context of religion-state relations showed a genuin form. Three of the most important theme in this period that take NU attention were  theme about the homeland, the basis of the state and the of authority president. all theme that seems to NU always bases itself on religious views. Religiousity is always used to measure, assess and participation to  the state  Keywords: Darul Islam, Fatwa bughot, Pancasila, Waliyul Amri Dhoruri bis-Saukah.